A Study on the Health Intervention of Zhao Bao Tai Chi for Special Populations: A Practical Analysis Based on Personal Military Injury Rehabilitation Experiences and Meridian Theory - Deng, Baolin (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details